A Study on the Students Ability in Identifying Verbal and Nominal Sentences at the Eighth Grade Student of SMP N 05 Bonai Darussalam - Despita; Puspa Gundary; Mohd. Rafi riyawi (DIMAR: Jurnal Pendidikan Islam, 2020)
This paper entitled “A Study on the Students Ability in Identifying Verbal and Nominal Sentences at the Eighth Grade Student of SMP N 05 Bonai Darussalam”. The research is a descriptive research, intended to know the students’ ability in constructing verbal and nominal sentences at eighth grade student of SMP N 05 Bonai Darussalam. The subject of this research is the eighth grade student of SMP N 05 Bonai Darussalam. The object of this research is the students’ ability constructing verbal and nominal sentence. The population of this research is the eighth grade student of SMP N 05 Bonai Darussalam. There is one class of population. Total numbers of students are 34.The researcher uses the total sampling. The result of this research showed that the student’s ability in constructing verbal and nominal sentences at eighth grade student of SMP N 05 Bonai Darussalam falls to good level. This can be seen on the results of the test conducted by the researcher. The researcher got the total score of the whole students is 2555. So, the average score of the students is 75,15. Based on the score above, student’s ability in constructing verbal and nominal sentences at eighth grade student of SMP N 05 Bonai Darussalam falls to good level.